The Role of the Notary in Resolving Disputes Regarding the Deed of Sale and Purchase Agreement (PPJB) (Case Study at the Notary/PPAT in Pekanbaru City) - Dwi Mutia Sari; Busyra Azheri; Jean Elvardi (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2023)
The subject matter of this research is the role of a notary in resolving disputes over the Sale and Purchase Agreement Deed (PPJB) made by the parties before him and how the legal force of peace made by the parties before a notary related to the dispute over the Sale and Purchase Agreement Deed (PPJB). This legal research uses an empirical juridical method, which is a method of approaching the problem by looking at the applicable legal norms and then connecting them with legal facts found in the field. While this type of research is descriptive-analytical, namely describing an event that occurs clearly and in detail. The results of the study, the role of a notary in resolving disputes in the Sale and Purchase Agreement Deed (PPJB) made by the parties in front of him the notary can act by providing input on the dispute between the parties in the deed made by the notary, this function is the role of the notary voluntarily as a parties who understands his duties and functions as a notary, and in this case, the notary is also considered to understand the core of the problems that are happening and the legal strength of the peace made by the parties before the notary regarding the dispute of the Sale and Purchase Agreement Deed (PPJB), namely the notary has such an important authority to provide legal counseling and provide information in connection with the making of authentic deeds.